1995
DOI: 10.1128/aem.61.2.690-697.1995
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the immunofluorescence procedure for detection of Giardia cysts and Cryptosporidium oocysts in water

Abstract: The accurate determination of the presence of Giardia cysts and Cryptosporidium oocysts in surface waters requires a reliable method for the detection and enumeration of these pathogenic organisms. Published methods have usually reported recovery efficiencies of less than 50% for both cysts and oocysts. Typically, the losses are greater for Cryptosporidium oocysts than they are for Giardia cysts. The purpose of this study was to examine procedures used for sample collection, elution, concentration, and clarifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
9

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 7 publications
4
42
0
9
Order By: Relevance
“…The mean recovery efficiency of the filter analysis procedure was 44.0 Ϯ 4.4% for Giardia cysts and 14.1 Ϯ 4.7% for Cryptosporidium oocysts ( n = 78 control filters). These recoveries compare favorably to the recoveries of 8.8% and 10.8%, respectively, reported by Clancy et al (11) in an interlaboratory comparison, and fit the pattern of recoveries of less than 50% with Cryptosporidium being the lowest that was identified by LeChevallier et al (12) The analytical results from Temagami North and South and from Thunder Bay, Loch Lomond, and Bare Point, are summarized in Table I. The raw and treated Temagami results are divided into "outbreak" and "postoutbreak" periods to show the marked increase in the number of cysts and the very high concentrations of Giardia cysts in both treated and raw water samples from Temagami South during the outbreak.…”
Section: Resultssupporting
confidence: 86%
“…The mean recovery efficiency of the filter analysis procedure was 44.0 Ϯ 4.4% for Giardia cysts and 14.1 Ϯ 4.7% for Cryptosporidium oocysts ( n = 78 control filters). These recoveries compare favorably to the recoveries of 8.8% and 10.8%, respectively, reported by Clancy et al (11) in an interlaboratory comparison, and fit the pattern of recoveries of less than 50% with Cryptosporidium being the lowest that was identified by LeChevallier et al (12) The analytical results from Temagami North and South and from Thunder Bay, Loch Lomond, and Bare Point, are summarized in Table I. The raw and treated Temagami results are divided into "outbreak" and "postoutbreak" periods to show the marked increase in the number of cysts and the very high concentrations of Giardia cysts in both treated and raw water samples from Temagami South during the outbreak.…”
Section: Resultssupporting
confidence: 86%
“…Giardia recoveries averaged 12% 2 18 using the USEPA method and 49% 2 91 using the Ongerth membrane method; Cryptosporidium recoveries averaged 8% 2 13 with the USEPA method and 9% 2 4 using the Ongerth membrane method. Other studies have reported higher recoveries (LeChevallier et al 1991(LeChevallier et al , 1995 but these recoveries are from seeded packed pellets which do not include the sampling and elution steps. The ICR method recoveries in this study were higher than previously reported (Clancy 1996) and may be due to sampling only a 10 l sample volume rather than the 100 l normally sampled.…”
Section: Discussionmentioning
confidence: 91%
“…Previous seeding and recovery studies frequently used (oo)cyst doses at concentrations of 10 4 -10 6 in order to achieve some detection of the target organisms (LeChevallier et al 1995;Clancy 1996). These levels are far in excess of the concentrations expected in natural samples.…”
Section: Discussionmentioning
confidence: 99%
“…However, Cryptosporidium detection levels currently used vary considerably and may either underestimate or overestimate actual viable and infective organism levels. [40][41][42] This analysis relies on extrapolation of a doseresponse relationship in healthy subjects to a broader population. A single, laboratory-stored strain of C. parvum was used in the dose-response experiments.…”
Section: Discussionmentioning
confidence: 99%